Searches for neutral Higgs bosons in e(+)e(-) collisions around root s=189 GeV - Abreu, P; Adam, W; Adye, T; Adzic, P; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; Amaldi, U; et al. (2000)
Searches for neutral Higgs bosons in the Standard Model and the MSSM have been performed using data collected by the DELPHI experiment at a centre-of-mass energy of 188.7 GeV, corresponding to an integrated luminosity of 158 pb-1. These analyses are used, in combination with our results from lower energies, to set new 95% confidence level lower mass bounds on the Standard Model Higgs boson (94.6 GeV/c2) and on the lightest neutral scalar (82.6 GeV/c2) and neutral pseudoscalar (84.1 GeV/c2) Higgs bosons in a representative scan of the MSSM parameters. The results are also interpreted in the framework of a general two-Higgs doublet model.